Rancang Bangun Sistem Alat Ukur Heart Rate Dan Suhu Tubuh Menggunakan Esp 8266 - Syhabudin, Noval Aziz; Darmawan, Budi; ‎Supriono, Supriono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research developed an Internet of Things (IoT)-based health monitoring system, which is designed to support real-time monitoring of heart rate and body temperature without the need for on-site medical personnel. The main problem identified is the need for health monitoring tools that can be used independently by the community to monitor health status simply and accurately. The device was developed using a ESP8266 microcontroller, a MAX30100 heart rate sensor, and a MLX90614 temperature sensor, allowing for the automatic collection of health data and the transmission of data through the Telegram application using a Wi-Fi network. Data sources come from many subjects with different ages and health. conditions to test the effectiveness and accuracy of the device. The method used involves testing sensors to measure heart rate and body temperature, with the data displayed on an OLED screen and transmitted in real time for remote monitoring. The results showed that the accuracy of the measurements was at a good level, with an average error of 5 to 7%. Linguistic analysis of the data showed the device's ability to detect serious health conditions such as hypoxemia (SpO2 < 95%) and hypothermia (body temperature < 36°C), requiring immediate medical attention. This solution allows individuals to easily perform health monitoring independently without the need for medical assistance.